Polarity-guided uneven mitotic divisions control brassinosteroid activity in proliferating plant root cells - Vukašinović, Nemanja; Hsu, Che-Wei; Marconi, Marco; Li, Shaopeng; Zachary, Christopher; Shahan, Rachel; Szekley, Pablo; Aardening, Ziv; Vanhoutte, Isabelle; Ma, Qian; Pinto, Lucrezia; Krupař, Pavel; et al. (Cell, 2025)
Brassinosteroid hormones are positive regulators of plant organ growth, yet their function in proliferating tissues remains unclear. Here, through integrating single-cell RNA sequencing with long-term live-cell imaging of the Arabidopsis root, we reveal that brassinosteroid activity fluctuates throughout the cell cycle, decreasing during mitotic divisions and increasing during the G1 phase. The post-mitotic recovery of brassinosteroid activity is driven by the intrinsic polarity of the mother cell, resulting in one daughter cell with enhanced brassinosteroid signaling, while the other supports brassinosteroid biosynthesis. The coexistence of these distinct daughter cell states during the G1 phase circumvents a negative feedback loop to facilitate brassinosteroid production while signaling increases. Our findings uncover polarity-guided, uneven mitotic divisions in the meristem, which control brassinosteroid hormone activity to ensure optimal root growth.
Keywords: single-cell RNA sequencing; proliferace buněk; Arabidopsis Proteins; meristém; Brassinosteroids; root meristem; brassinosteroids; signální transdukce; Plant Growth Regulators; Signal Transduction; proteiny huseníčku; Mitosis; mitóza; polarita buněk; Plant Roots; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; cell cycle; cell polarity; Cell Proliferation; Cell Polarity; Arabidopsis; regulátory růstu rostlin; live-cell imaging; cell division; kořeny rostlin; Meristem; brassinosteroidy